2012
DOI: 10.4028/www.scientific.net/amm.249-250.1214
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Household Appliances Controller in Smart Home

Abstract: The system based on the Internet of Things thought will be the direction of the future smart home. The paper designed a unified household appliances controller which is the core of the smart home system. It adopts RTL8019AS Ethernet controller to realize embedded Internet by which users can have access to remote control. And it uses maturing wireless Bluetooth technology to complete the communication between the controller and the sub-controlling system. S3C2410 is the embedded processor and μC/OS-II is the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In the field of clinical cardiology, one study has shown that deep learning algorithms clearly outperform clinicians in predicting prognosis and future events in patients with pulmonary hypertension [30]. With the development of IoT technology, IoT will gradually become the basis of home appliances [31]. To sum up, many artificial intelligence diagnostic algorithms have been developed to detect diseases, but their prediction accuracy for hypertension is lower.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of clinical cardiology, one study has shown that deep learning algorithms clearly outperform clinicians in predicting prognosis and future events in patients with pulmonary hypertension [30]. With the development of IoT technology, IoT will gradually become the basis of home appliances [31]. To sum up, many artificial intelligence diagnostic algorithms have been developed to detect diseases, but their prediction accuracy for hypertension is lower.…”
Section: Introductionmentioning
confidence: 99%
“…The network layer has been constructed to process and transfer all of the information acquired in the perception layer through the mobile communication system or internet etc. The application layer is able to analyze and process all of the information acquired in the perception layer and the transmission network to make correct control and decision for the intelligent management, application and services [4].…”
Section: Introductionmentioning
confidence: 99%
“…are used to identify things and collect information. In the network domain, information acquired in the sensing domain can be processed and transferred through the mobile communication system and the internet etc, while in the application domain, information will be analyzed and processed to server for the correct control and decision making for the purpose to achieve the intelligent management, application and service [2].…”
Section: Introductionmentioning
confidence: 99%